2015
DOI: 10.4314/ahs.v15i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting disclosure of serostatus to children attending Jinja Hospital Paediatric HIV clinic, Uganda

Abstract: Abstract:Background: Disclosure of HIV status is important for optimal adherence to antiretroviral therapy in children. Identifying factors that affect disclosure of sero-status to children will help improve the process of disclosure. The purpose of the study was to determine the rate of HIV disclosure by the parents/caretakers to their children and other factors affecting disclosure. Methods: A cross sectional study among 174 caretakers of children age 5-18 years, twenty children and all (ten) health workers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
40
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 22 publications
9
40
1
Order By: Relevance
“…In addition, parents/guardians fear that the child could have negative emotional consequences after their diagnosis has been disclosed to them. Similar studies [ 27 , 16 , 21 , 19 , 28 ], have reported that parents fear that the child will cry, be sad, run away, harm themselves and lose hope.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In addition, parents/guardians fear that the child could have negative emotional consequences after their diagnosis has been disclosed to them. Similar studies [ 27 , 16 , 21 , 19 , 28 ], have reported that parents fear that the child will cry, be sad, run away, harm themselves and lose hope.…”
Section: Discussionmentioning
confidence: 57%
“…This discrepancy may have been contributed by complete lack of standardized national training for paediatric HIV disclosure that varied in content and duration [ 16 , 20 ]. Similar studies have reported missing contents in paediatric HIV disclosure training including on the appropriate age and maturity level to initiate the process of disclosure [ 21 ]. WHO has recommended that paediatric HIV disclosure training for healthcare providers should cover the following vital areas: stigma, privacy, culturally appropriate disclosure process, communication based on child’s age, HIV information to parents/guardians and children, emotional preparation and management, responding to children’ concerns, and planning for the future [ 22 ].…”
Section: Discussionmentioning
confidence: 83%
“…Disclosing to HIV-infected children about their HIV sero-positive status (i.e. informing HIV-infected children that they have HIV) has been associated with proper adherence to medications and can help children to cope with the stresses associated with HIV infection [ 6 , 7 , 9 , 14 , 16 ]. However, studies suggest that HIV status disclosure is often delayed until after 10 years of age because it is believed that prior to this age children will not be able to understand the information or deal with the stigma associated with the diagnosis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar barriers to disclose by parents/ caregivers as reported by HCWs include: parents' fear of being blamed by their children, parents feeling guilty and fear that the child will tell others, 24,25 child being too young and cannot keep secret, 20 and social stigma surrounding the HIV diagnosis. 25 Other studies 3,14,20,26,27 however reported different reasons which include: fear of the child crying, fear of being very sad, fear of the child run away, and fear of him or herself losing hope.…”
Section: Methodsmentioning
confidence: 99%